Eosinophilic esophagitis-associated epithelial remodeling may limit esophageal carcinogenesis - Fuller, Annie D.; Karami, Adam L.; Kabir, Mohammad Faujul; Klochkova, Alena; Jackson, Jazmyne L.; Mu, Anbin; Tan, Yinfei; Klein-Szanto, Andres J.; Whelan, Kelly A. (Frontiers in Allergy, 2023)
Under homeostatic conditions, esophageal epithelium displays a proliferation/differentiation gradient that is generated as proliferative basal cells give rise to suprabasal cells then terminally differentiated superficial cells. This proliferation/differentiation gradient is often perturbed in esophageal pathologies. Basal cell hyperplasia may occur in patients with gastroesophageal reflux disease (GERD), a condition in which acid from the stomach enters the esophagus, or eosinophilic esophagitis (EoE), an emerging form of food allergy. While GERD is a primary risk factor for esophageal cancer, epidemiological data suggests that EoE patients do not develop esophageal cancer. In order to investigate the impact of EoE and esophageal cancer specifically on the cellular landscape of esophageal epithelium, we perform single cell RNA-sequencing in murine models of EoE and esophageal cancer, specifically esophageal squamous cell carcinoma (ESCC). In mice with either EoE or ESCC, we find expansion of cell populations as compared to normal esophageal epithelium. In mice with EoE, we detect distinct expansion of 4 suprabasal populations coupled with depletion of 2 basal populations. By contrast, mice with ESCC display unique expansion of 2 basal populations and 1 suprabasal population, as well as depletion of 2 suprabasal populations. We further evaluated modules of co-expressed genes in EoE- and ESCC-enriched epithelial cell clusters. Senescence, glucocorticoid receptor signaling, and granulocyte-macrophage colony-stimulating factor pathways were associated with EoE-enriched clusters while pathways associated with cell proliferation and metabolism were identified in ESCC-enriched clusters. Finally, by pairing murine models of EoE and ESCC, we demonstrate that exposure to EoE inflammation limits esophageal carcinogenesis. Our findings provide the first functional investigation of the relationship between EoE and esophageal cancer and suggest that esophageal epithelial remodeling events occurring in response to EoE inflammation may limit esophageal carcinogenesis. This investigation may have future implications for leveraging allergic inflammation-associated alterations in epithelial biology to prevent and/or treat esophageal cancer.